2002
DOI: 10.1136/thorax.57.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and carers' preferences in two models of care for acute exacerbations of COPD: results of a randomised controlled trial

Abstract: Background: A study was undertaken to investigate quality of life in asthma, defined by differing criteria, to see which may be most appropriate in epidemiological studies. Methods: The 426 adults were participants in the follow up phase of the European Community Respiratory Health Survey (ECRHS) in Melbourne. As part of the laboratory visit, participants completed the SF-36 quality of life questionnaire, a detailed respiratory questionnaire, and underwent lung function testing. Results: Both the physical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 13 publications
2
106
0
1
Order By: Relevance
“…A first feasibility analysis of home-based services to prevent conventional hospitalization of COPD exacerbations was reported in 1999 by Gravil and collegues (Gravil et al, 1998). Subsequent controlled trials confirmed both safety and cost reduction when these types of services were applied to selected COPD patients (Cotton et al, 2000;Davies et al, 2000;Hernandez et al, 2003;Ojoo et al, 2002;Skwarska et al, 2000).…”
Section: Current Knowledge On Home Care For Copd Exacerbationsmentioning
confidence: 99%
“…A first feasibility analysis of home-based services to prevent conventional hospitalization of COPD exacerbations was reported in 1999 by Gravil and collegues (Gravil et al, 1998). Subsequent controlled trials confirmed both safety and cost reduction when these types of services were applied to selected COPD patients (Cotton et al, 2000;Davies et al, 2000;Hernandez et al, 2003;Ojoo et al, 2002;Skwarska et al, 2000).…”
Section: Current Knowledge On Home Care For Copd Exacerbationsmentioning
confidence: 99%
“…In one RCT, unvalidated questionnaires were used, but the study was too small to provide robust evidence about differences between the HaH and inpatient schemes that were being compared. 24 In practice, using questionnaires to measure patient satisfaction is difficult -patients' responses are heavily influenced by the framing of questions and how they are asked 25 and by the patients' own expectations and beliefs. 26 Because of these difficulties The Picker Institute Europe (www.pickereurope.org/ index.php) advocate questionnaires to capture patient experience rather than satisfaction.…”
Section: Patient and Carer Satisfactionmentioning
confidence: 99%
“…For the patient satisfaction instrument used by Ojoo and referred to in the previous section, the summary measures were proportions Evaluating early discharge schemes for COPD S Taylor et al satisfied (88% in the conventional care and 92% in the HaH group). 24 When two different types of care are being compared evaluators are advised to seek advice from a statistician about suitable analyses, since there are many, and they depend on the type of outcome and the question being asked. In the Skwarska study, the difference in time to readmission appeared to reflect a real difference that would be likely to be seen in similar patients whereas the difference in proportions readmitted appeared to be due to chance.…”
Section: Sample Size and Analysis Of Quantitative Datamentioning
confidence: 99%
“…A majority of patients prefer domiciliary over hospital care [12], leading to greater patient satisfaction [13]. Thus, spirometry in the primary care setting can be an important example of this demand-driven care.…”
Section: Figurementioning
confidence: 99%